The Relationship between Servant Leadership, Organisational Citizenship Behaviour and Team Effectiveness: Exploring the Impact of Servant Leadership on Teacher Teams in Public Sector Organizations (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Associations progressively use groups so as to build their upper hand, improve profitability, upgrade imagination, increment reaction times and improve basic leadership (Afolabi, Adesina and Aigbedion, 2009 Schlechter and Strauss, 2008 Sheng and Tian, 2010 Wong, Tjosvold and Liu, 2009). It can, thusly, be contended that powerful group working is one of the significant determinants of organizational achievement. Albeit various investigations on group adequacy in associations exist, little has been done on teacher groups in open area associations.